2011
DOI: 10.1001/archgenpsychiatry.2011.55
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Depression Care Management and Disparities in Depression Treatment and Outcomes

Abstract: Context Collaborative depression care management (DCM), by addressing barriers disproportionately affecting patients of racial/ethnic minority and low education, may reduce disparities in depression treatment and outcomes. Objective To examine the effect of DCM on treatment disparities by education and ethnicity among older depressed primary care patients. Design, Setting and Participants Analysis of data from a randomized controlled trial known as PROSPECT (Prevention of Suicide in Primary Care Elderly: C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 62 publications
1
39
0
Order By: Relevance
“…Our results suggest that after initially seeking treatment, these individuals continue to experience a worse course of depression over a long follow-up period. Collaborative depression care management, which incorporates use of a care coordinator, has shown promise in improving depression outcomes among individuals with low education and those who experience other barriers to effective treatment (Bao et al, 2011).…”
Section: Baseline Predictors Of Depression Coursementioning
confidence: 99%
“…Our results suggest that after initially seeking treatment, these individuals continue to experience a worse course of depression over a long follow-up period. Collaborative depression care management, which incorporates use of a care coordinator, has shown promise in improving depression outcomes among individuals with low education and those who experience other barriers to effective treatment (Bao et al, 2011).…”
Section: Baseline Predictors Of Depression Coursementioning
confidence: 99%
“…28 That racial minority status is associated with lower use of mental health services may also explain the slightly lower risk of HRM use in blacks and other non-white groups. [29][30][31] More research is needed to better elucidate the process by which these gender and racial differences arise.…”
Section: Commentsmentioning
confidence: 99%
“…For example, programs of therapeutic education especially tailored for this population should be developed, as they have been for treatment of other illnesses (57,58). Previous American studies have shown that depression care management programs (involving a care manager who conducts patient assessment, education, follow-ups, and care coordination) can be effective in reducing social inequalities in depression treatment and outcomes (50,59); such programs should be tested elsewhere to reduce social inequalities in depression management.…”
Section: Discussionmentioning
confidence: 99%
“…General practitioners may find it more difficult to diagnose depression and assess its severity among these patients (45)(46)(47)(48)(49). Moreover, low-SES patients may manage their illness and adhere to treatment poorly; they may have a greater expectation, for example, that the drug will work immediately, although it takes several weeks for antidepressants to become effective (50). Social inequalities in patientphysician communication, as shown in other health fields (26,51,52), may worsen this situation.…”
Section: Social Inequalities In Early Discontinuation Of Antidepressantsmentioning
confidence: 99%